BERPENGARUHKAH DESENTRALISASI FISKAL DAN KINERJA PEMERINTAH DAERAH TERHADAP AKUNTABILITAS PELAPORAN KEUANGAN? - Elva Dona; Gentha Gautama; Irwan Muslim (Sekolah Tinggi Pariwisata Mataram, 2022)
Financial reporting accountability is an obligation of the government to provide accountability for regional financial reports. The purpose of this study is to determine the effect of fiscal decentralization and local government performance on financial reporting accountability in 19 districts and cities of West Sumatra Province. The sample in this study were 19 regencies and cities of West Sumatra Province with the sampling technique of total sampling. The analytical method used is binary logistic regression method. Based on the hypothesis, the research results simultaneously show that fiscal decentralization and local government performance have a positive effect on financial reporting accountability. Partially that fiscal decentralization has a positive effect on financial reporting accountability, local government performance has no effect on financial reporting accountability.